2016
DOI: 10.4236/me.2016.712133
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of CEO Compensation before and after the Financial Crisis

Abstract: This paper revisits the determinants of CEO compensation using recent data (covering 125 firms from 2003 to 2012). We focus in particular on how CEO pay changed after the 2008 financial crisis. Post-crisis, the composition of pay shifted away from cash toward equity. Furthermore, post-crisis pay is tied more closely to performance and less closely to factors (like firm size) that are more tenuously connected to shareholder value. We also investigate the impact of mergers and divestitures on CEO pay, overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 34 publications
6
25
0
Order By: Relevance
“…The aforementioned relation also appears in Himmelberg and Hubbard (2000), Terviö (2008), Gabaix and Landier (2008), Chen (2017), Jung and Subramanian (2017) and, from a more critical point of view, in Elson and Ferrere (2013). Sonenshine et al (2016) offer a review on this issue.…”
Section: Related Literaturementioning
confidence: 94%
See 2 more Smart Citations
“…The aforementioned relation also appears in Himmelberg and Hubbard (2000), Terviö (2008), Gabaix and Landier (2008), Chen (2017), Jung and Subramanian (2017) and, from a more critical point of view, in Elson and Ferrere (2013). Sonenshine et al (2016) offer a review on this issue.…”
Section: Related Literaturementioning
confidence: 94%
“…The relation between executive compensation and firm performance has also been subject to debate, being possible to identify two points of view: "pay for performance" and "pay without performance." For instance, Sonenshine et al (2016Sonenshine et al ( , p. 1475) state that the financial crisis appears to have altered the determinants of CEO compensation toward pay for performance versus other factors (such as firm size). Rosen (1992), Hall and Liebman (1998), Core et al (2003), Bertrand (2009), Frydman and Jenter (2010) and Essen et al (2012) seem also close to the "pay for performance" standpoint, whereas Fried (2004, 2005), Djankov et al (2008), or Bell and Van Reenen (2016) place the emphasis on the "pay without performance" perspective; for example, for Bebchuk and Fried (2005), managerial power has played a key role in shaping executive pay.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature on board independence also highlights the role of independent directors in increasing the corporate innovation (Balsmeier, Fleming, & Manso, 2017; Lu & Wang, 2018). There are many studies which highlight the role of independent directors on crucial board decisions such as anti-takeover defences (Byrd & Hickman, 1992), restructuring (Johnson, Hoskisson, & Hitt, 1993), corporate social responsibility (Zhang, Zhu, & Ding, 2013) executive compensation (Sonenshine, Larson, & Cauvel, 2015; Vafeas, 2000) and impacts stock volatility (Christy, Matolcsy, Wright, & Wyatt, 2013), IPO’s valuation (Bertoni, Meoli, & Vismara, 2014) and cost of debt (Bradley & Chen, 2015), but no study has examined their signalling role on institutional investor’s ownership.…”
Section: Introductionmentioning
confidence: 99%
“…
Because the 2008/2009 economic crisis forced companies to reassess how their business operations were conducted, it is envisaged that, as part of this reassessment, the attitudes about determining executive remuneration changed as well to be more in line with company performance (Sonenshine, Larson, & Cauvel, 2016). Furthermore, Yang, Dolar andMo (2014) found that the link between business performance and chief executive officers' (CEOs) remuneration depicts different types of patterns in the pre-and post-crisis periods.
…”
mentioning
confidence: 99%